Antimicrobial susceptibility pattern and distribution of Staphylococcal cassette chromosome mec among methicillin-resistant coagulase-negative staphylococci - Saber Abu Bakr Saleh, Huda (2018)
Coagulase-negative staphylococci (CoNS) are notorious in causing nosocomial infections. Staphylococcus epidermidis is deemed the most significant species infecting human, apart from Staphylococcus haemolyticus and Staphylococcus chromogenes. In Malaysia, there is an increasing trend of antimicrobial resistance among CoNS whereby more than 50% has been reported as methicillin-resistant coagulase-negative staphylococci (MR-CoNS) which these organisms harbour mecA gene which is acquired by a mobile genetic element in staphylococci called staphylococcal cassette chromosome mec (SCCmec). This study aims to investigate species distribution among 100 MR-CoNS, to determine antimicrobial susceptibility pattern among the species and to detect their SCCmec types. Coagulase-negative staphylococci (CoNS) isolated from blood cultures were collected from Microbiology laboratory, Hospital Serdang in year 2016 and proceeded to phenotypic identification by gram-staining, catalase and coagulase test. Species identification was done by using API® Staph kit. Antimicrobial susceptibility testing (AST) was performed by using Kirby-Bauer method with nine antibiotic discs and was interpreted following Clinical and Laboratory Standards Institute (CLSI) 2016. Detection of SCCmec was performed by using multiplex polymerase chain reaction (PCR). Staphylococcus epidermidis (n=56, 56%) was the most common species isolated in this recent study, followed by S. haemolyticus (n=19, 19%), S. chromogenes (n=12, 12%), Staphylococcus xylosus (n=6, 6%), Staphylococcus hominis (n=5, 5%), Staphylococcus capitis (n=1, 1%) and Staphylococcus cohnii (n=1, 1%). All isolates were resistant to cefoxitin (n=100, 100%) and penicillin (n=100, 100%). More than 80% of the isolates were resistant to erythromycin and 70% were resistant to fucidic acid. All isolates were sensitive to vancomycin. A total of 54 (54%) isolates harboured SCCmec type IVa (n=32, 32%) in which was widely distributed in S. epidermidis (n=27, 48.2%). Fifteen (15%) isolates showed combination types which the most common was type I & IVa (n=9, 9%) and another 31 strains (31%) were non-typeable. Type IVa was observed to have multiple antibiotic resistance with high rates of resistance towards erythromycin (n=32, 100%) followed by fucidic acid (n=25, 78.1%) and clindamycin (n=24, 75%). In conclusion, S. epidermidis was the most common isolated species. Apart from penicillin, high percentages of resistance towards erythromycin and fucidic acid were observed in this recent study. This is probably due to the high usage of these antibiotics in outpatient clinical setting. Type IVa was the most detected SCCmec with multiple antibiotic resistance harbouring.